The role of α-, 3(10)-, and π-helix in helix→coil transitions - Armen, Roger (Cold Spring Harbor Laboratory Press, 2003)
The conformational equilibrium between 3(10)- and α-helical structure has been studied via high-resolution NMR spectroscopy by Millhauser and coworkers using the MW peptide Ac-AMAAKAWAAKA AAARA-NH2. Their 750-MHz nuclear Overhauser effect spectroscopy (NOESY) spectra were interpreted to reflect appreciable populations of 3(10)-helix throughout the peptide, with the greatest contribution at the N and C termini. The presence of simultaneous αN(i,i + 2) and αN(i,i + 4) NOE cross-peaks was proposed to represent conformational averaging between 3(10)- and α-helical structures. In this study, we describe 25-nsec molecular dynamics simulations of the MW peptide at 298 K, using both an 8 Å and a 10 Å force-shifted nonbonded cutoff. The ensemble averages of both simulations are in reasonable agreement with the experimental helical content from circular dichroism (CD), the (3)J(HNα) coupling constants, and the 57 observed NOEs. Analysis of the structures from both simulations revealed very little formation of contiguous i → i + 3 hydrogen bonds (3(10)-helix); however, there was a large population of bifurcated i → i + 3 and i → i + 4 α-helical hydrogen bonds. In addition, both simulations contained considerable populations of π-helix (i → i + 5 hydrogen bonds). Individual turns formed over residues 1–9, which we predict contribute to the intensities of the experimentally observed αN(i,i + 2) NOEs. Here we show how sampling of both folded and unfolded structures can provide a structural framework for deconvolution of the conformational contributions to experimental ensemble averages.